Respuesta :
Answer:
Step-by-step explanation:
hello,
[tex]15x^2-10x=15(x^2-\dfrac{10}{15}x)=15(x^2-\dfrac{2}{3}x)[/tex]
and we can write that
[tex](x-\dfrac{2}{2*3})^2=(x-\dfrac{1}{3})^2=x^2-\dfrac{2}{3}x+\dfrac{1}{9}[/tex]
so
[tex]x^2-\dfrac{2}{3}x= (x-\dfrac{1}{3})^2-\dfrac{1}{9} \ so\\15x^2-10x=15(x^2-\dfrac{2}{3}x)=15[(x-\dfrac{1}{3})^2-\dfrac{1}{9} ]=15(x-\dfrac{1}{3})^2-\dfrac{15}{9}\\=15(x-\dfrac{1}{3})^2-\dfrac{5}{3}[/tex]
Then
[tex]15x^2-10x+\dfrac{5}{3}=15(x-\dfrac{1}{3})^2[/tex]
then, I would say that you need to add 5/3 to make a perfect square
hope this helps